The Uremic Toxin Homocysteine Exacerbates the Brain Inflammation Induced by Renal Ischemia-Reperfusion in Mice - Eun Jung Park; Jihyun Je; Theodomir Dusabimana; Seung Pil Yun; Hye Jung Kim; Hwajin Kim; Sang Won Park (Biomedicines, 2022)
Homocysteine (Hcy), a homologue of cysteine, is biosynthesized during methionine metabolism. Elevated plasma Hcy is associated with glomerular injury and considered as a risk factor for renal dysfunction, predicting incident chronic kidney disease. Hcy promotes oxidative stress, inflammation, and endothelial dysfunction. Acute kidney injury (AKI) is defined as a sudden decline in renal function and is important clinically due to the high mortality rate in AKI patients with multiple organs failure, including the brain. However, the cytotoxic role of Hcy on the brain following AKI is not directly shown. In this study, C57BL/6 mice were subjected to renal ischemia reperfusion (IR), one of the causes of AKI, and treated with vehicle or Hcy (0.2 mg/kg) to analyse the brain inflammation. IR mice showed a significant induction in plasma creatinine and Hcy levels, associated with tubular injury and neutrophil infiltration, and upregulation of pro-inflammatory cytokines and tubular apoptosis. Hcy treatment aggravated these renal damage and dysfunction by regulating cyclooxygenase-2 (COX-2), inhibitor of κB phosphorylation, and heme oxygenase-1. Consistently, Hcy treatment significantly increased expression of pro-inflammatory cytokines, glial fibrillary acidic protein, and COX-2 in the prefrontal cortex of IR mice. We conclude that Hcy treatment aggravated the renal dysfunction and enhanced IR-induced inflammatory cytokines and astrocyte activation in the brain. We propose that lowering plasma Hcy levels may attenuate neurological dysfunction found in patients with AKI.